2015
DOI: 10.1186/s13567-015-0153-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of host – Peste des petits ruminants vaccine viral transcriptome uncovers transcription factors modulating immune regulatory pathways

Abstract: Peste des petits ruminants (PPR), is an acute transboundary viral disease of economic importance, affecting goats and sheep. Mass vaccination programs around the world resulted in the decline of PPR outbreaks. Sungri 96 is a live attenuated vaccine, widely used in Northern India against PPR. This vaccine virus, isolated from goat works efficiently both in sheep and goat. Global gene expression changes under PPR vaccine virus infection are not yet well defined. Therefore, in this study we investigated the host-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 64 publications
(71 reference statements)
2
47
0
Order By: Relevance
“…PBMCs were used in vitro to study the innate immune responses in sheep and goats in response to BTV infection [18]. Recently, global transcriptome analysis was used to understand the molecular events of host virus interactome in PPRV [19], Measles virus [20], [21] and Rinderpest virus [21] infections. However, to the best of our knowledge there are currently no reports on global transcriptome analysis of BTV-host interactome till date.…”
Section: Introductionmentioning
confidence: 99%
“…PBMCs were used in vitro to study the innate immune responses in sheep and goats in response to BTV infection [18]. Recently, global transcriptome analysis was used to understand the molecular events of host virus interactome in PPRV [19], Measles virus [20], [21] and Rinderpest virus [21] infections. However, to the best of our knowledge there are currently no reports on global transcriptome analysis of BTV-host interactome till date.…”
Section: Introductionmentioning
confidence: 99%
“…Among the cells subject to PPRV infection, Vero cells are usually used to study PPRV infection in vitro [17,44]. It is well known that PPRV can infect a multitude of host cells, such as sheep kidney epithelial cells [45] (PO cell line) and goat peripheral blood mononuclear cells (PBMCs) [46]. Throughout our study, caprine endometrial epithelial cells were used for the experiments, and we showed that PPRV can successfully replicate in caprine EECs, further confirming the clinical phenomenon of abortions in PPRV-infected goats [3,4]; these data thus provide a theoretical basis for the replication mechanism of PPRV.…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenic and nonpathogenic RPV also induce significant differences, with the latter inducing a slightly higher interferon response as well as significant effects on the transcription of genes involved in cell cycle regulation [Nanda et al, 2009]. PPRV infection to PBMCs leads to differential expression of at least 985 genes that are involved in regulating immune regulatory, spliceosomal and apoptotic pathways [Manjunath et al, 2015]. Previously, with a traditional reductionist approach, only handfuls of these genes were known.…”
Section: Genome-wide Changes In Host Genes Following Virus Infectionmentioning
confidence: 99%
“…Computational analyses have been used to construct and describe virus-host interactomes [Watanabe and Kawaoka, 2015] which in turn have identified cellular targets for therapeutic intervention [Kumar et al, 2011a]. Such host-virus interactomes have been generated for a wide variety of viruses, including PPRV [Manjunath et al, 2015], and have highlighted the cellular factors that may be important in viral replication, virulence, pathogenesis and immune response [Law et al, 2013]. A metaanalysis of virus-host interactomes identified both common as well as virus-specific host targets, suggesting that a common drug target for multiple viruses can be developed [Watanabe and Kawaoka, 2015].…”
Section: Virus-host Interactomesmentioning
confidence: 99%
See 1 more Smart Citation